Theoretical Modeling and Experimental Verification of Mechanical Properties of Natural Fiber Reinforced Thermoplastics. (2015) - Munde, Yashwant S.; Ingle, Ravindra. B.
Abstract: Development of biocomposites has a wide interest as inexpensive and minimum environmental pollution. The present research work focused on study the mechanical properties of biocomposite using available theoretical models and experimental verification of mechanical properties. The theoretical model used are parallel & series, Halpin-Tsai, modified Halpin-Tsai and Hirsch model for evaluation of mechanical tensile properties (Tensile strength & Tensile modulus). Compression molding machine (hot press type) technique was used for preparation of sample specimens. Experimental mechanical characterization carried out as per ASTM D638 -01 using universal testing machine. Evaluated tensile modulus and tensile strength results of theoretical models are compared with experimental results of mechanical characteristics.